Efficient bioconversion of enzymatic corncob hydrolysate into biomass and lipids by oleaginous yeast Rhodosporidium paludigenum KM281510. Issue 6 (3rd July 2019) - Chaiyaso, Thanongsak; Manowattana, Atchara; Techapun, Charin; Watanabe, Masanori
Abstract: This study aims to valorize of enzymatic corncob hydrolysate (ECH) for biomass and lipid productions via microbial bioconversion by the efficient oleaginous yeast Rhodosporidium paludigenum KM281510. Biomass (5.63 g/L), lipids (3.29 g/L), and lipid content (58% (g/g)) were observed by batch cultivation in shaking flask. The effect of total sugar concentration in ECH, agitation rate, temperature, and initial pH were investigated in both batch and fed-batch cultivations by shaking flask and 3.0 L airlift bioreactor. Biomass, lipids, and lipid content of 27.77 g/L, 20.27 g/L, and 70% (g/g) were obtained with 100 g/L total sugar (68 g/L glucose, 29 g/L xylose, and 3 g/L arabinose), pH 6.5, 25 °C, 6.0 vvm, for 7 days by batch cultivation in bioreactor. Surprisingly, production parameters were improved by fed-batch, wherein these promising high biomass (36.06 g/L), lipid production (25.12 g/L), and lipid productivity (2.52 g/L/d) values were achieved. Moreover, fed-batch cultivation promoted the utilization of xylose (2.5-times) and arabinose (3.4-times) higher than batch cultivation, achieving lipid content (70% (g/g)) with oleic acid (53%). These results would be helpful for understanding the comprehensive utilization of ECH, especially the pentose sugars, for growth and lipogenesis of oleaginous yeast as well as being a qualified biodiesel feedstock.